Is shorting of Exchange Traded Funds a dangerous financial sport? recent UK evidence - Mohamad, Azhar (2013)
An Exchange Traded Fund (ETF) is a security that tracks a basket of stocks. An ETF investor gains immediate exposure to the basket, by taking either a long or short position on this instrument. Both hedgers and speculators can short ETFs, making the informational content of increases in ETF short interest difficult to interpret. Using high frequency (daily) short interest data for ETFs traded on the London Stock Exchange between June 2006 and April 2010, we examine the price impact on ETFs of increases in short interest. Contrary to most of the previous empirical evidence for individual stocks, we find that large increases in ETF short interest are associated with subsequent over-performance relative to a benchmark index and this pattern is most pronounced during pre-financial crisis period.